(untitled) (Bangladesh Medical Journal, 2019)
Cardiovascular diseases (CVDs) emerging as a major health problem in Bangladesh due to increase prevalence of risk factors. Conventional cardioprotective drugs are effective but expensive and associated with a number of side effects. Curcuma longa is an important source of traditional medicine for the prevention and treatment of CVDs. The objective of the study was to evaluate the protective effect of Curcuma longa on isoproterenol induced myocardial injury in rats. This experimental study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka during 2015. Total 21 Wistar albino male rats, aged 85 to 100 days, weighing 100 to 150 g (initial body weight) were selected for the study. After acclimatization for 14 days, the rats were divided into three groups. Group A (base line control group), Group B (isoproterenol treated control group) and Group C (Curcuma longa pretreated and isoproterenol treated group). Each group consisted of 7 rats. On the 10th day of experiment, rats were sacrificed after taking final body weight. Blood samples were collected from the heart. Serum aspartate aminotransferase (AST) level was estimated by Colorimetric method and lactate dehydrogenase (LDH) level was estimated by ELISA method. The statistical analysis was done by one way ANOVA and Bonferroni test as applicable. In this study, the mean initial and final body weight of the rats were almost similar and showed no statistically significant difference among the groups. The mean serum AST and LDH levels were significantly (P<0.001) higher in Group B than those of Group A. Again, these levels were significantly (P<0.001) lower in Group C than those of Group B group. From the results, it can be concluded that Curcuma longa has cardioprotective activity on isoproterenol induced myocardial injury in Wistar albino rats. Bangladesh Med J. 2018 Jan; 47 (3): 13-17